Circular RNAs in the Brain: A Possible Role in Memory?. (October 2021) - Zajaczkowski, Esmi L.; Bredy, Timothy W.
Higher-order organisms possess information processing capabilities that are only made possible by their biological complexity. Emerging evidence indicates a critical role for regulatory RNAs in coordinating many aspects of cellular function that are directly involved in experience-dependent neural plasticity. Here, we focus on a structurally distinct class of RNAs known as circular RNAs. These closed loop, single-stranded RNA molecules are highly stable, enriched in the brain, and functionally active in both healthy and disease conditions. Current evidence implicating this ancient class of RNA as a contributor toward higher-order functions such as cognition and memory is discussed.